LAKU TASAWUF ORANG TUA UNTUK PENCAPAIAN KECERDASAN MORAL DAN SPIRITUAL ANAK - Ulil Hidayah (STAI Ma'had Aly Al-Hikam Malang, 2020)
Sufism is a morality that is used by Sufis to draw closer to God through practices of worship and penance. The aim of the approach taken by the Sufis is to find calm and tranquility in living life with all the achievements it hopes for. Sufism is also a practice for lay people to take part in as the goal of achieving the desired expectations. Like parents who also have hopes for the achievement of their child's success, parents make various efforts to have smart children. One of the efforts made beyond his limits is to get closer to the perpetrator of Sufism with the essence that determines everything. In this study, the variables studied were emotional and spiritual intelligence in children through Sufism behavior by their parents. Researchers conducted qualitative descriptive research techniques to explore data about how Sufism was carried out by parents to realize their desire to have children who were emotionally and spiritually intelligent and described them with analysis tools. The object of this research is the parents as guardians of students of Madrasah Diniyah Nurul Falah in Ranubedali Village Ranuyoso Lumajang.